2008
DOI: 10.1080/07373930802467490
|View full text |Cite
|
Sign up to set email alerts
|

Kaffir Lime Leaf (Citrus hystricDC.) Drying Using Tray and Heat Pump Dehumidified Drying

Abstract: Desorption isotherms of mature kaffir lime leaves are determined and a nonlinear regression program was applied to the experimental data to fit with any of the four moisture sorption isotherm models. It was found that the modified Halsey model could fit the best. Tray and heat pump-dehumidified drying of kaffir lime leaves were conducted and it was found that the modified Page model was the most effective one. The drying constant was fitted to drying air temperature using the Arrhenius model. Effective moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 29 publications
2
30
2
Order By: Relevance
“…The results agreed with the previous research (Phoungchandang et al 2003;2009;Phoungchandang and Saentaweesuk 2011). The exponent (N) was added to drying constant and drying time of the NT model to increase the dependence of temperature and relative humidity of the drying air (Phoungchandang 2008;Phoungchandang et al 2008a, b;2009). The K values increasing with temperature obtained from HPD were higher than that from TD because of the lower RH of drying air at the same drying temperature (Table 5).…”
Section: Modeling Of Drying Kinetics Of C Asiatica Leavessupporting
confidence: 81%
See 4 more Smart Citations
“…The results agreed with the previous research (Phoungchandang et al 2003;2009;Phoungchandang and Saentaweesuk 2011). The exponent (N) was added to drying constant and drying time of the NT model to increase the dependence of temperature and relative humidity of the drying air (Phoungchandang 2008;Phoungchandang et al 2008a, b;2009). The K values increasing with temperature obtained from HPD were higher than that from TD because of the lower RH of drying air at the same drying temperature (Table 5).…”
Section: Modeling Of Drying Kinetics Of C Asiatica Leavessupporting
confidence: 81%
“…(17) and Table 5). They were determined by fitting the experimental data in terms of ln(MR) versus t (Chottanom and Phoungchandang 2005;Phoungchandang et al 2008a, b;2009;Potisate and Phoungchandang 2010). The results revealed that microwave blanching and higher drying temperature provided higher D eff in both TD and HPD.…”
Section: Modeling Of Drying Kinetics Of C Asiatica Leavesmentioning
confidence: 99%
See 3 more Smart Citations